Pengaruh Kualitas Laporan Keuangan Terhadap Kepercayaan Publik di Lingkungan Pemerintah Provinsi Sumatera Barat - Hadi, Lalu Adiyatma Taopikul; Sahbany, Sri (Indo-MathEdu Intellectuals Journal, 2026)
The background of this research arises from the importance of transparency and accountability in regional financial management as a basis for building public legitimacy regarding government performance. This study aims to analyze the effect of the quality of financial reports on the level of public trust within the West Sumatra Provincial Government. The research method used is qualitative descriptive with a field study approach through interviews and the distribution of questionnaires to 55 respondents consisting of the general public, academics, and regional government officials. Primary data was obtained through in-depth interviews. Data analysis was carried out using an interactive model that includes three main stages: data reduction, data presentation, and drawing conclusions. The research results indicate that the quality of financial reports has a positive relationship with public trust. The aspects of openness and relevance of information are dominant factors contributing to increased public confidence, while the aspect of ease of understanding remains a major obstacle because financial reports are considered too technical and difficult for non-accounting audiences to comprehend. These findings affirm that the quality of financial reports depends not only on data accuracy but also on the government's ability to present information communicatively and transparently.